Plankton diversity and aquatic ecology of a freshwater lake (L3) at Bharti Island, Larsemann Hills, east Antarctica - Pawan K. Bharti; U.K. Niyogi (Global Journal of Environmental Science and Management)
The Larsemann Hills range is an ice-free oasis on the Ingrid Christensen Coast of Princess Elizabeth Land, East Antarctica, which includes Bharti Island, Fisher Island, McLeod Island, Broknes Peninsula, Stornes Peninsula, and several other islands, promontories, and nunataks. The Larsemann Hills is an ice-free area of approximately 50 km2, located halfway between the Vestfold Hills and the Amery Ice Shelf on the south-eastern coast of Prydz Bay, Princess Elizabeth Land, East Antarctica. The ice-free area consists of two major peninsulas (Stornes and Broknes), four minor peninsulas, and approximately 130 near shore islands. The Larsemann Hills area contains more than 150 lakes at different Islands and peninsulas. Bharti Island of Larsemann Hills in east Antarctica was selected as a sampling site for the present study. Water sample was collected from a freshwater lake during XXXth Indian Scientific Expedition to Antarctica (ISEA) and analyzed for the physico-chemical parameters, major elements, trace metals and major plankton diversity in surface lake water by following standard methodology. The concentrations of metals Cu, Pb, Cd, Zn and Cr were measured using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES). Phytoplankton and zooplankton were also assessed in the aquatic ecosystem of Lake L3 at Bharti Island, Larsemann Hills over east Antarctica. Psychrophillic bacteria were found 71 cfu in lake water, while total bacterial count was found to be 5.4 × 102cfu.